Comprehensive characterisation of the active ingredients of Smilax glabra Roxb based on chemical fingerprinting, metabolic fingerprinting and pharmacodynamic fingerprinting - Shi, Wenqing; Jia, Mengqi; Li, Xiao; Zhao, Xin; Wang, Chenxi; Fan, Guorong; Lou, Yuefen (Frontiers in Pharmacology, 2025)
BackgroundSmilax glabra Roxb (SGR) is a traditional Chinese medicine known for its medicinal and edible properties, with a long history of clinical use in treating hyperuricemia (HUA). However, current research has primarily focused on ethanol extracts, leaving the active ingredients and mechanisms responsible for the uric acid-lowering effects of SGR standard decoction unclear.MethodsFirstly, the chemical components in the standard decoction of SGR were characterized by ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS), and the pharmacodynamic experiments in mice with a high uric acid model were used to rapidly screen out the uric acid-lowering active ingredient group. Secondly, metabolic fingerprinting and tissue distribution analysis were performed on plasma and tissue samples from rats orally administered with SGR, respectively, to identify the key components and target organs. Finally, the core targets of these active ingredients were screened and analyzed by molecular docking technology.ResultsWe fractionated the ingredients of the SGR standard decoction into large and medium polar compound groups using macroporous resin, identifying 20 components. Then, through the pharmacodynamic experiment in hyperuricemic mice, we verified that the group of medium polar compounds in SGR had significant uric acid-lowering effects. In the metabolic fingerprinting analysis, 8 flavonoids and 24 metabolites were screened in the plasma of SD rats. Tissue distribution analysis revealed that the liver, intestine, kidney, and stomach were the main target organs for the active ingredients, with neoastiblin, astilbin, neoisoastiblin, isoastiblin, engeletin, and metabolites M01, M08, and M15 being the most widely distributed. Molecular docking confirmed that metabolites M08, M11, M15, and M16 exhibited strong binding activities with the target proteins CNT2, XOD, and URAT1.ConclusionThis study provides valuable references and insights into the pharmacodynamic substance basis and mechanism of action of SGR standard decoction for HUA treatment, through comprehensive analyses of chemical, metabolic, and pharmacodynamic fingerprints.